A Dynamic Reactive Power Allocation Method for Sending-End Power System of the UHVDC Delivering Large Terminal of Renewable Energy. (4th February 2023) - Li, Yecheng; Guo, Pengcheng; Zhuang, Wenbin; Li, Zhiqiang; Huo, Chengxiang; Zhang, Jiahuan; Yue, Lei; Xue, Ancheng
Abstract : Allocation of reactive power equipment can relieve the transient overvoltage, which is a big threat to the sending-end electric power system of ultrahigh-voltage direct current (UHVDC). However, the dynamic reactive power allocation mostly depends on the trial-and-error method, lacking in an optimal allocation method based on the quantitative evaluation index. To deal with the abovementioned problem, in this study, a dynamic reactive power optimal allocation method is proposed based on the reactive power compensation sensitivity. In detail, first, based on the existing transient overvoltage assessment index, the general form of reactive power optimization problem is proposed. Then, taking the sending-end power system of UHVDC as an example, the reactive power allocation location is determined based on a reactive power compensation sensitivity. Furthermore, combined with the sensitivity, the compensation capacity of each place is determined by particle swarm optimization (PSO). The simulation results show that the proposed method can effectively allocate the dynamic reactive power and suppress the transient overvoltage after fault.